The Determinants Influencing Behavioral Intention in Consuming Halal Food Among Muslim Students of University Wijaya Kusuma Surabaya - Khoirul Anam; Betania Kartika Muhflih; Mohammad Aizat Jamaludin; Susilo Wati (Amorti: Jurnal Studi Islam Interdisipliner, 2023)
The study aimed to understand what influences Muslim students' intention to consume halal food at University Wijaya Kusuma in Surabaya, Indonesia. It considered factors like attitude, subjective norms, perceived behavioral control, religiosity, and government initiatives. Through questionnaires collected from 452 students, the research found that religiosity, subjective norms, and attitude significantly affected students' intentions to consume halal food.